Finite-time active fault-tolerant attitude control for flexible spacecraft with vibration suppression and anti-unwinding. Issue 9 (1st May 2023) - Hasan, Muhammad Noman; Haris, Muhammad; Qin, Shiyin
Abstract: In this paper, a finite-time active fault-tolerant control scheme is designed for a flexible spacecraft's attitude control experiencing inertial parametric variations, external disturbances, multiple actuator faults, and estimation errors while suppressing the flexible appendages' vibrations without using smart vibration suppression actuators. First, relative attitude dynamics of a flexible spacecraft with multiple actuator faults are outlined, and a sliding mode observer is designed to estimate flexible appendages-related vibrations. The proposed fault detection and identification (FDI) strategy can efficiently detect actuator faults, avoiding the false alarms caused by uncertainties and disturbances, and accurately estimate the cumulative fault effects on the spacecraft via Chebyshev neural network (CNN) based estimator. Based on a novel fast nonsingular terminal sliding mode surface, a finite-time, unwinding-free, and adaptive fault-tolerant attitude controller is designed to acclimatize the detected faults and uncertainties effectively, also heeding the errors in the estimation of flexible modes and faults. The spacecraft can carry out the coveted control objective in a definable time, and the stability of the proposed controller is corroborated via Lyapunov techniques. Finally, a comparative simulation analysis with the existing results elucidated the proposed scheme's efficacy.